Design innovations for contemporary interiors and civic art - Crespi, Luciano (Advances in media, entertainment, and the arts (AMEA) book series, 2017)
This book examines novel techniques in structural designs in various cultural and social scenarios, featuring innovative application methods, emergent trends, and research on tools being utilized in the field.